Аntisecretory Treatment of Diarrhea in Children - Ye.I. Yulish (Zaslavsky O.Yu., 2014)
The paper presents the current data on the incidence, causes, major pathogenetic mechanisms of acute diarrhea in children. The authors considered therapeutic approaches to the control of secretory diarrhea, new pathogenetic agents for its treatment.